The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jpm.12524
|View full text |Cite
|
Sign up to set email alerts
|

Coping amidst an assemblage of disadvantage: A qualitative metasynthesis of first‐person accounts of managing severe mental illness while homeless

Abstract: There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it. This is the peer reviewed version of the following article Karadzhov, D., Yuan, Y. and Bond, L. (2020) Coping amidst an assemblage of disadvantage: a qualitative metasynthesis of first-person accounts of managing severe mental illness while homeless.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 90 publications
(222 reference statements)
1
13
0
1
Order By: Relevance
“…As such, working relationships that are grounded in trust, respect, fairness and honesty are key to providing recovery-oriented care to currently and formerly homeless people with mental illness. Moreover, as many people with mental illness and histories of homelessness have limited social ties and networks (Hawkins & Abrams, 2007; Karadzhov et al, 2020; Pahwa et al, 2019), the relationships developed in service settings may partially compensate for unmet social needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, working relationships that are grounded in trust, respect, fairness and honesty are key to providing recovery-oriented care to currently and formerly homeless people with mental illness. Moreover, as many people with mental illness and histories of homelessness have limited social ties and networks (Hawkins & Abrams, 2007; Karadzhov et al, 2020; Pahwa et al, 2019), the relationships developed in service settings may partially compensate for unmet social needs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, conceptualizations of recovery have largely neglected how poverty may restrict people from living the lives that they want (Padgett et al, 2016; Sylvestre et al, 2018). For example, research has shown that homelessness and adulthood victimization are detrimental to recovery (Castellow et al, 2015; Karadzhov et al, 2020; Kerman, Sylvestre, et al, 2019; Stumbo et al, 2015). Further, the stability provided by safe and affordable housing, with the necessary supports, can be the foundation to recovery for people with serious mental illness (Kirkpatrick & Byrne, 2009; Padgett, 2007; D.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of homelessness, however, those recovery-promoting processes are often severely disrupted (e.g. Karadzhov, Yuan, & Bond, 2019). For many, homelessness is a profoundly alienating and dehumanising experience, which can impede the individual's capabilities of maintaining meaningful social relationships.…”
Section: Analysis Of Personal Recoverymentioning
confidence: 99%
“…However, PEH with SMI have incredibly high needs and health disparities. [2][3][4][5][6][7][8][9][10] Little is known about similarities and differences in pathways to homelessness for patients with and without psychiatric illness. One study suggests that PEH with mental illness have similar pathways to homelessness as their peers without psychiatric problems.…”
Section: Discussionmentioning
confidence: 99%